The impact of vaccination upon dental clinic avoidance and the cessation of individual protection measures - González-Olmo, Maria Jose; Diego, Rafael Gómez de; Delgado-Ramos, Bendición; Romero-Maroto, Martin; Carrillo-Diaz, María (Frontiers in Public Health, 2022)
The aim of this study was to analyze the evolution of germ aversion, to perceived infectability and to the fear of COVID-19 from the beginning of the pandemic until the arrival of the vaccines. A repeated measures design was used with three time points during the pandemic. The survey consisted of: Scale of perceived vulnerability to disease; Scale of fear of COVID-19; They were asked if they were vaccinated and if that vaccination is complete. They were asked if they would avoid the dental clinic through fear of COVID-19; and if they have reduced preventive practice in response to COVID-19. A T0-T1 increase in perceived infectability and germ aversion was reported. However, fear of COVID-19 decreased at T1-T2. The vaccinated experienced a greater reduction than the unvaccinated and a greater relaxation of their preventive practice. The frequency of dental avoidance decreased in the vaccinated group from T1 to T2 by 68.3% while in the non-vaccinated this reduction was only 4.9%; X2 = 18.58 (p < 0.01). In summary, vaccination has had an impact in the reduction of perceived infectability and in reducing fear of COVID-19. Nevertheless, germ aversion has remained stable and independent of vaccination. Empirical support is found for the affirmation that vaccination can reduce certain preventive behavior and dental avoidance.